Cloud-Assisted EHR Sharing With Security and Privacy Preservation via Consortium Blockchain - Wang, Yong; Zhang, Aiqing; Zhang, Peiyun; Wang, Huaqun (IEEE access, 2019)
The sharing of electronic health records (EHRs) has great positive significance for research of disease and doctors' diagnosis. In recent years, cloud-based electronic medical record sharing scheme has brought a lot of conveniences, but the centralization of cloud exposes threats inevitably to data security and privacy preservation. Blockchain technology can be seen as a promising solution to address these problems on account of its unique propertis of decentration, anonymity, unforgeability and verifiability. In this paper, we propose a blockchain based secure and privacy-preserving EHR sharing protocol. Data requester can search desired keyword from data provider to find relevant EHRs on the EHR consortium blockchain and get the re-encryption ciphertext from cloud server after getting the data owner's authorization. The scheme mainly uses searchable encryption and conditional proxy re-encryption to realize data security, privacy preservation, and access control. Furthermore, proof of authorization is designed as the consensus mechanism for consortium blockchain to guarantee system's availability. Security analysis demonstrates that the proposed protocol can achieve security goals. Besides, we emulate the cryptographic primitives and implement the proposed scheme on Ethereum platform. Performance evaluation shows that the proposed scheme has high computational efficiency.